Environmental Impact of Tourism Development Activities Within Gashaka Gumti National Park - Silas, Akafa Konde; Madaki, Kanati; Chibuma, Gani Saidu (Darul Yasin Al Sys, 2025)
Tourism is one of the fastest growing sectors of the global economy and exerts significant positive and negative impacts on the environment, culture, society, and economy. While it can contribute to the development of host communities, unregulated tourism often threatens the very environmental resources on which it depends. This study focuses on assessing the environmental impacts of tourism in and around Gashaka Gumti National Park, with the objective of understanding both the beneficial and adverse consequences of tourist activities on natural resources and the physical environment. A sample of 100 respondents was collected through a convenient sampling method, supplemented by direct observation of environmental conditions. Findings highlight that although tourism can promote environmental protection and conservation through awareness and economic incentives, it also generates pressures such as resource depletion, pollution, and degradation of the physical landscape. The study emphasizes the need for ecotourism strategies, balanced resource use, and proper planning to ensure that tourism development remains environmentally sustainable, socially beneficial, and economically viable. It concludes that a carefully managed tourism sector can minimize adverse effects while enhancing conservation and community development in Gashaka Gumti National Park.